Debatable issues in Fiqh al-Zakat: a jurisprudential appraisal - Haneef, Sayed Sikandar Shah (Hamdard Foundation Press, Pakistan, 2010)
Introduction Since early 20th century, some leading scholars have been fervently debating the possibility of making fresh ijtihÉd on a host of newly emerging issues of fiqh al-zakÉt. This is asserted to be so due to radical changes that have taken place in the methods of producing new forms of wealth and the way that the Muslims deal even with the traditionally designated zakÉt payable wealth. There are many issues1 that have engaged serious scholarly debates surrounding the fiqh of zakÉt. But for the purpose of this paper, we briefly highlight the current debate about issues, such as the adequacy of growth as the criterion for zakÉtablity of the wealth, contemporary definition of niÎÉb, attempts at revising the rate of zakÉt, calculation of the hawl, and exemptible assets of the zakÉt payer. In this study therefore, different views for reform shall be examined with the prime idea of offering a jurisprudentially valid position on the about mooted points.